CaO‐MgO‐Al2O3‐SiO2 corrosion behavior of SrZrO3‐La2Ce2O7 composite ceramics. Issue 3 (8th January 2022) - Ma, Wen; Qi, Yingwei; Liu, Ying; Gao, Yuanming; Bai, Yu; Jia, Ruiling; Dong, Hongying; Wang, Ruijun; Bao, Manyu
Abstract: In this work, the corrosion behavior, interaction products, and the corrosion mechanism of (1‐ x )SrZrO3 ‐ x La2Ce2O7( x = 0.3, S7L3; x = 0.5, S5L5; x = 0.7, S3L7) composite bulks after CaO‐MgO‐Al2 O3 ‐SiO2 (CMAS) attack at 1250°C for 1, 4, and 12 h were investigated, respectively. The molten CMAS and the bulks rapidly interacted and generated a dense reaction layer, which mainly composed of La‐Ce apatite, Ce2 Zr2 O7.04, ZrO2 with some Ce, Ca, Si, Mg, and Al elements preventing CMAS from continuous penetration effectively. The formation of CMAS self‐crystallizing products such as Ca2 Al2 SiO7 gehlenite and Mg‐Al spinel with high melting points increased the viscosity of CMAS. The elements in the ceramic also diffused into the molten CMAS and formed Ce2 Zr2 O7.04 and La2 Ce2 O7, increasing the melt viscosity and blocking the penetration channel of the molten CMAS. The S5L5 bulk has the best corrosion resistance against CMAS attacks.